2020
DOI: 10.1155/2020/9608910
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Gail Model to Predict the Risk of Developing Breast Cancer among Jordanian Women

Abstract: Background and Objectives. Breast cancer has been the most common cancer affecting women in Jordan. In the process of implementing breast cancer prevention and early detection programs, individualized risk assessment can add to the cost-effectiveness of such interventions. Gail model is a widely used tool to stratify patients into different risk categories. However, concerns about its applicability across different ethnic groups do exist. In this study, we report our experience with the application of a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In a study similar to our study results, it was found that BSE behavior was significantly higher in women who had a family history than those who did not. 29 The reason why age was found to be an effective factor in our study may be because women feel the risk of cancer more as they get older, and therefore they perform BSE regularly. In addition, the genetic risk in women or the presence of a friend with BC in their environment may have made them more susceptible to performing regular BSE.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a study similar to our study results, it was found that BSE behavior was significantly higher in women who had a family history than those who did not. 29 The reason why age was found to be an effective factor in our study may be because women feel the risk of cancer more as they get older, and therefore they perform BSE regularly. In addition, the genetic risk in women or the presence of a friend with BC in their environment may have made them more susceptible to performing regular BSE.…”
Section: Discussionmentioning
confidence: 69%
“…Although BSE is easy and free to apply, the application rates in countries are low and vary by country. 5,[29][30][31] According to the results of our study, the majority of women performed BSE regularly, and age, education level, and family history of cancer affected BSE behavior. In a study similar to our study results, it was found that BSE behavior was significantly higher in women who had a family history than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Family history was the primary factor in determining breast cancer risk. The use of the Gail model was shown to detect only 17.3% of women if the score was determined five years before a diagnosis [ 14 ]. This shows a limitation of the Gail score in that it was developed to measure breast cancer risk in a population of American women.…”
Section: Introductionmentioning
confidence: 99%